2022
DOI: 10.1128/msystems.00312-22
|View full text |Cite
|
Sign up to set email alerts
|

Apex Predator Nematodes and Meso-Predator Bacteria Consume Their Basal Insect Prey through Discrete Stages of Chemical Transformations

Abstract: The processes by which organic life is consumed and reborn in a complex ecosystem were investigated through a multiomics approach applied to the tripartite Xenorhabdus bacterium- Steinernema nematode- Galleria insect symbiosis. Trophic analyses demonstrate the primary consumers of the insect are the bacteria, and the nematode in turn consumes the bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Trp metabolism is crucial for pathogen and host microbiota interactions. Although there has been relatively little research in the field of insects, it has recently been found that in tripartite Xenorhabdus bacterium-Steinernema nematode-Galleria insect symbiosis, the Trp metabolism pathway, especially the Kyn pathway, plays important functions at different stages (Mucci et al, 2022). We discovered that after S. feltiae-X.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Trp metabolism is crucial for pathogen and host microbiota interactions. Although there has been relatively little research in the field of insects, it has recently been found that in tripartite Xenorhabdus bacterium-Steinernema nematode-Galleria insect symbiosis, the Trp metabolism pathway, especially the Kyn pathway, plays important functions at different stages (Mucci et al, 2022). We discovered that after S. feltiae-X.…”
Section: Discussionmentioning
confidence: 89%
“…Trp metabolism is crucial for pathogen and host microbiota interactions. Although there has been relatively little research in the field of insects, it has recently been found that in tripartite Xenorhabdus bacterium- Steinernema nematode- Galleria insect symbiosis, the Trp metabolism pathway, especially the Kyn pathway, plays important functions at different stages ( Mucci et al, 2022 ). We discovered that after S. feltiae - X. bovienii were injected into the hemocoel of G. mellonella , the Trp metabolic pathway of the insects was significantly upregulated, especially the 3-HAA content of the Kyn pathway, which was significantly increased in the treated group.…”
Section: Discussionmentioning
confidence: 99%
“…As part of their symbiotic and entomopathogenic lifecycle, all Xenorhabdus must colonize and be transported by a nematode host, suppress insect immunity, establish a community within and consume the cadaver, and support reproduction of the nematode to ensure future transport [10]. Many will also compete or cooperate with other resident or transient hermaphroditum, currently the most genetically tractable steinernematid [24,120,25].…”
Section: Discussionmentioning
confidence: 99%
“…The resultant insect cadaver is an enclosed nutrient-rich niche that both nematode and bacterium leverage to reproduce proliferatively. Nematode fecundity is enhanced by the consumption of Xenorhabdus [10], and Xenorhabdus defends the niche by secreting bacteriocins, antimicrobials and scavenger deterrents, which antagonize both microbial and invertebrate competitors [11][12][13]. Before their exit from the insect cadaver and entry into the surrounding soil, nascent IJ nematodes are specifically colonized by Xenorhabdus in the anterior intestine and ultimately, the receptacle [14].…”
Section: Introductionmentioning
confidence: 99%
“…Once invading an insect, IJ releases its symbiotic bacteria, and both partners kill the insect. Xenorhabdus bacteria replicate using the nutrient from the insect cadaver and the bacteria serve as food for the nematodes (Mucci et al, 2022), supporting their reproductive development (juveniles J1-J4 and adults). The depletion of nutrients and nematode overcrowding within the dead insect, causing accumulation of pheromone, could induce IJ development, and promote IJs disperse from the insect cadaver into the soil to seek for a new insect prey (Kaplan et al, 2012; Popiel et al, 1989) (Fig.…”
Section: Introductionmentioning
confidence: 99%